2016
DOI: 10.1111/jvs.12407
|View full text |Cite
|
Sign up to set email alerts
|

Comparing an exotic shrub's impact with that of a native life form analogue: Baccharis halimifolia vs Tamarix gallica in Mediterranean salt marsh communities

Abstract: Nomenclature Tison & de Foucault (2014) for vascular plants, Julve AbstractQuestions: To what extent may impact vary according to the invaded community, region or sites? Do impact thresholds exist, above which native species richness and/or cover declines rapidly? Does impact following invasion by the exotic shrub Baccharis halimifolia differ from that of a native shrub (Tamarix gallica) during natural successions?Location: Mediterranean coast, SE France.Methods: Vegetation was sampled on 120 4-m² quadrats, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Fried and Panetta (2016) found that native species' responses to invasion were complex and, in general, non-linear across a gradient of B. halimifolia cover. Species richness declined linearly with increasing B. halimifolia cover (indicating a non-threshold relationship), whilst the abundance of native perennial forbs and graminoids declined significantly only when B. halimifolia exceeded 80%, i.e.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fried and Panetta (2016) found that native species' responses to invasion were complex and, in general, non-linear across a gradient of B. halimifolia cover. Species richness declined linearly with increasing B. halimifolia cover (indicating a non-threshold relationship), whilst the abundance of native perennial forbs and graminoids declined significantly only when B. halimifolia exceeded 80%, i.e.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
“…Several other studies have also provided evidence for negative impact thresholds for a variety of invasive plants, including the shrub Baccharis halimifolia in Mediterranean saltmarshes (Fried and Panetta 2016), the monocarpic perennial Heracleum mantegazzianum in northern European grasslands (Thiele et al 2010b), the vine Delairea odorata in northern Californian coastal scrub and riparian communities (Alvarez and Cushman 2002), and the scrambling herbs Tradescantia fluminensis, Plectranthus ciliatus and Asparagus scandens in New Zealand temperate forests (McAlpine et al 2015). Fried and Panetta (2016) found that native species' responses to invasion were complex and, in general, non-linear across a gradient of B. halimifolia cover.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative environmental impacts of alien plants are indeed typically density‐dependent (Richardson et al ., , ; Bímová et al ., ; Staska et al ., ; Fried & Panetta, ); the formation of dense populations occurs more with perennial than annual plants, especially tall perennials (Hejda et al ., ). There are, however, exceptions for alien species hybridizing with native species, which may pose a high risk even at low densities (Daehler & Strong, ; Huxel, ; Wolf et al ., ).…”
Section: Methodsmentioning
confidence: 99%